Factors Influencing Project Owner Satisfaction with Supervision Consultants in Public Building Projects - Aulia, Hafizah; Irfan, Prasetia; Retna, Hapsari Kartadipura (International Journal of Engineering and Management Sciences, 2025)
The construction supervision consultant is an appointed party responsible for overseeing the implementation of construction projects from start to finish. The satisfaction level of project owners with the consultant’s performance is a key indicator of project success. This study aims to determine the level of satisfaction and key factors influencing it in public building projects. A quantitative method was employed by distributing questionnaires to respondents from the Public Works Office, particularly within the Cipta Karya Division in Tapin Regency, which serves as the case study location. Data were analyzed using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. The results showed that overall, the consultant’s performance was rated as very satisfactory, with the highest CSI score on the communication indicator (86.64%) and the ability to ensure and improve work quality (85.33%). The lowest CSI score was found in the documentation/administration indicator (80.11%). Although the CSI score indicates a high level of satisfaction, there is still room for improvement, particularly in administrative aspects and understanding of technical regulations. The IPA analysis also shows that several indicators fall under top priority, such as documentation/administration, supervision, internal human resources, communication, and the ability to ensure and enhance work quality. The improvement strategies proposed include training, high discipline, and effective communication.